ECONOMIC IMPACTS OF EU–BELARUSIAN TRADE - Miškinis, Algirdas; Dultsau, Ihar (Ekonomika, 2012)
The main goal of the research is to assess the efficiency of Belarus–EU trade and to develop an econometric model to find out which goods Belorus should export in order to ensure its GDP growth. Authors have made an analysis of the main trade theories, reviewed the common EU trade policy, determined a relationship between Belarusian trade in goods with the EU and its economic growth, studied the consequences of the potential free trade agreement with the EU. The research used secondary data that have been analysed by means of a system of indicators, the matrix method, and regression correlation analysis. The analysis revealed that the trade balance between Belarus and the EU in most years has been negative, that the degree of trade concentration between Belarus and the EU is low, and that trade between the two parties has both intra-industry and inter-industry features. The econometric model has revealed a negative impact of the Belarusian export of agricultural products and iron and steel on its GDP growth rate. The study has also shown that so far it is difficult to forecast the timelines and consequences of Belarus–EU free trade agreement.